FAKTOR YANG BERHUBUNGAN DENGAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN DI PUSKESMAS DAHLIA - Nur Qamariyah; Nursyamsiyah Nursyamsiyah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2021)
In today's human civilization, all aspects of life cannot be separated from organization, because by nature humans are social creatures who tend to always live in society. This is seen well in household life, social organizations, especially when someone enters the world of work. This person will interact and become part of the organization where he works. This research aims to determine the relationship between leadership style and employee performance, work environment, work communication, and employee job satisfaction at the Dahlia Community Health Center, Makassar City. The type of research used is the Observation method with a Cross Sectional Study design. The sampling technique in this research is Exchautive Sampling Technique (total sample). Data analysis using the chi square test. The research results show that there is a relationship between employee performance and leadership style. There is a relationship between the work environment and leadership style. There is no relationship between communication and leadership style. There is a relationship between job satisfaction and leadership style. The conclusion of this research is that employee performance, work environment, and job satisfaction are related to leadership style, while work communication is not related to leadership style.